LAFADZ-LAFADZ DOA DALAM Al- QURAN - Utari, Eka Budi (Universitas Islam Negeri Sumatera Utara, 2024)
AbstractAllah SWT created humans as the best of his creations, however, behind perfection, humans still have shortcomings, therefore humans need support as a place to complain, plead and be anchored from the hustle and bustle of life in this world. In the Al-Quran itself we find many lafadz-lafadz which means prayer or there are also many prayers offered by the Prophets, apostles of Allah and also pious people, from the research results it was found that there are not any of these lafadz-lafadz prayers In the Koran, it is material but immaterial, meaning that none of these prayers ask for worldly possessions but rather requests and requests to achieve happiness in this world and the hereafter. Keywords: Lafadz Doa, Doa Dalam Al-Quran